Analisis Fluktuasi Nilai Tukar dan Suku Bunga Terhadap Harga Saham Sektor Pertambangan di Indonesia - Martin, Alnov; Roeytashya, Jasica; Felicia, Sheren; Florensia, Erika (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Stock prices in Indonesia’s mining sector are strongly influenced by macroeconomic factors, particularly the exchange rate of the Indonesian rupiah against the United States dollar (USD/IDR) and the benchmark interest rate set by Bank Indonesia (the BI 7-Day Reverse Repo Rate). Exchange rate fluctuations have the potential to increase foreign exchange risk for export-oriented mining companies, while changes in interest rates can affect the cost of capital and investment decisions. This study aims to analyze the impact of exchange rate and interest rate fluctuations on the stock prices of mining sector companies listed on the Indonesia Stock Exchange. The data used consist of monthly secondary data for the period 2020–2024 obtained from Bank Indonesia, the Indonesia Stock Exchange, and Statistics Indonesia. The research method employed is multiple linear regression with classical assumption tests to examine the relationship between the independent variables (exchange rate and interest rate) and the dependent variable (mining sector stock prices). The results of this study are expected to provide a theoretical contribution to the development of capital market literature, as well as practical considerations for investors and policymakers in formulating investment strategies in the mining sector.